2022
DOI: 10.1001/jamanetworkopen.2022.28002
|View full text |Cite
|
Sign up to set email alerts
|

Association of Placenta Previa With Severe Maternal Morbidity Among Patients With Placenta Accreta Spectrum Disorder

Abstract: IMPORTANCE Placenta previa is widely acknowledged as a risk factor for placenta accreta spectrum (PAS) disorders, which are severe maternal complications; however, data are limited regarding whether placenta previa is associated with a higher risk of worse maternal outcomes among patients with PAS disorders. OBJECTIVETo examine the association between placenta previa and the risk of severe maternal morbidities (SMMs) and higher resource use among patients with PAS disorders. DESIGN, SETTING, AND PARTICIPANTSTh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…The three main selection criteria were developed for one-step conservative surgery: (1) the absence of vesicouterine fibrosis, (2) the presence of at least 2 cm of healthy myometrium above the cervix, and (3) more than 50% of the axial uterine circumference. The second criterion, relating to patients with cervix or uterine segment involvement, was in accordance with our own study in which we identified an association between PAS complicated with placenta previa and severe maternal morbidity 16 . With 3,793 PAS cases recorded in the National Inpatient Sample Database, it is clear that we need to develop specific interventions to alleviate maternal and surgical morbidities for this particular subgroup of PAS patients.…”
Section: The Role Of Clinical Evaluation In the Selection Of Surgical...supporting
confidence: 69%
See 1 more Smart Citation
“…The three main selection criteria were developed for one-step conservative surgery: (1) the absence of vesicouterine fibrosis, (2) the presence of at least 2 cm of healthy myometrium above the cervix, and (3) more than 50% of the axial uterine circumference. The second criterion, relating to patients with cervix or uterine segment involvement, was in accordance with our own study in which we identified an association between PAS complicated with placenta previa and severe maternal morbidity 16 . With 3,793 PAS cases recorded in the National Inpatient Sample Database, it is clear that we need to develop specific interventions to alleviate maternal and surgical morbidities for this particular subgroup of PAS patients.…”
Section: The Role Of Clinical Evaluation In the Selection Of Surgical...supporting
confidence: 69%
“…The second criterion, relating to patients with cervix or uterine segment involvement, was in accordance with our own study in which we identified an association between PAS complicated with placenta previa and severe maternal morbidity. 16 With 3,793 PAS cases recorded in the National Inpatient Sample Database, it is clear that we need to develop specific interventions to alleviate maternal and surgical morbidities for this particular subgroup of PAS patients. With further investigation and validation, it should be possible for surgeons to stratify cases of PAS in an objective manner while also protecting fertility requirements.…”
Section: The Role Of Clinical Evaluation In the Selection Of Surgical...mentioning
confidence: 99%
“…22 In tertiary hospitals, over 75% of patients with SPPH had antenatal PPH high-risk factors, particularly PAS, which is associated with a higher risk of overall maternal and surgical morbidities. 23 PAS, first reported in 1927 with an incidence of only 0.12 in 1000 women, 24 has risen about 13-fold due to a rapidly increasing rate of CS deliveries, 25 and it may increase to 1 in 200 women by 2025. 26 With the widespread use of prenatal ultrasound examinations, most cases of PAS were recognised and referred to higher-level hospitals.…”
Section: Results and Clinical And Research Implicationsmentioning
confidence: 99%
“…In recent decades, the global prevalence of PAS has increased from 0.01 to 1.1% [ 2 ]. Unmanageable and catastrophic hemorrhage is the most common and serious complication of PAS since it may easily lead to hysterectomy, hemorrhagic shock, and even maternal-fetal death [ 3 , 4 ]. PAS is strongly associated with the history of cesarean section (CS) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%